Model Imre Lakatos dalam Studi Hadist: Pendekatan Epistimologis Terhadap Konteks dan Pembaharuan Keilmuan Islam - Musallamah, Qoni'ah (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article proposes a new methodological approach in hadith studies by integrating Imre Lakatos's research programme model into Islamic scholarship. This approach emerges in response to the dominant normative tendency in hadith studies, which often results in stagnation when confronting contemporary socio-cultural dynamics. Utilizing the hard core as the inviolable foundation of divine revelation, the protective belt as a flexible interpretative space, and the series of theories as the progressive development of hadith thought, the Imre Lakatos model enables a scientific reconstruction of hadith understanding that remains grounded in textual authority while remaining open to renewal. This study employs a literature review method, drawing from philosophical, methodological, and contemporary Islamic sources. The findings indicate that Lakatos’s methodology not only offers a strong epistemological foundation for hadith studies but also provides a conceptual instrument for building critical, rational, and context-sensitive Islamic research programmes. Accordingly, this article contributes to the advancement of Islamic studies that are more reflective, adaptive, and relevant to the challenges of the modern era.